The prevalence of burnout and its relationship with capital types among university staff in Tehran, Iran: A cross-sectional study - Irandoost, Seyed Fahim (Heliyon, 2021)
BACKGROUND: Burnout is a job-related syndrome that is common among university staff, and it is caused by various factors. The purpose of this study was to investigate the prevalence of burnout and its relationship with capital types among university staff in Tehran, Iran. METHODS: A cross-sectional descriptive-analytical design was used in which 420 staff were randomly sampled from the Iran University of Medical Sciences. For data collection, the researchers used the Burnout Inventory of Maslach and Jackson and Capital Types Questionnaire. The data were entered into SPSS software (Version 22) and analyzed by descriptive and inferential statistics and regressions. RESULTS: The mean burnout of staff was 84.42, and 45.9% of them had high burnout. A significant relationship was found among capital types, work experience, gender, education, and burnout. Multiple linear regressions also showed that independent variables estimated about 32% of the variance of the dependent variable, social capital, gender, and work experience, contributed more to explaining and predicting burnout index. CONCLUSION: Regarding the relationship between burnout and capital types (economic, cultural, and social), it is necessary to increase capital by increasing cultural activities, staff's knowledge level, income levels, informal groups, and finally, strengthening interpersonal relationships among staff.